Gaming Instead of Training? Exergaming Induces High-Intensity Exercise Stimulus and Reduces Cardiovascular Reactivity to Cold Pressor Test - Ketelhut, Sascha; Ketelhut, Reinhard G.; Kircher, Eva; Röglin, Lisa; Hottenrott, Kuno; Martin-Niedecken, Anna Lisa; Ketelhut, Kerstin (Frontiers in Cardiovascular Medicine, 2022)
Introduction The present study assessed if an exercise session in an innovative exergame can modulate hemodynamic reactivity to a cold pressor test (CPT) to a similar extent as a typical moderate endurance training (ET). Furthermore, cardiorespiratory, and affective responses of an exergame session and an ET were compared. Methods Twenty-seven healthy participants aged 25 ± 4 years (48% female; BMI 23.0 ± 2.1 kg/m2) participated in this cross-sectional study. All participants completed both an ET on a treadmill and training in the ExerCube (ECT). HR and oxygen consumption were recorded during both training sessions. Before and after both exercise sessions, the hemodynamic reactivity to a CPT was determined. Results During ECT, HR, oxygen consumption, energy expenditure, and the metabolic equivalent of the task were significantly higher than those obtained during ET (p < 0.001). With regard to the CPT, the participants showed significantly lower responses in peripheral systolic (p = 0.004) and diastolic blood pressure (p = 0.009) as well as central systolic (p = 0.002) and diastolic BP (P = 0.01) after ECT compared to ET. The same was true for pulse wave velocity (p = 0.039). Conclusion The ECT induced a significantly higher exercise stimulus compared to the ET. At the same time, it attenuated hemodynamic stress reactivity. The ECT presents a relevant training stimulus that modulates cardiovascular reactivity to stress, which has been proven as a predictor for the development of hypertension. Trial Registration ISRCTN registry, ISRCTN43067716, 14 April 2020, Trial number: 38154.